Penerapan Mediasi Penal Oleh Advokat Sebagai Konsep Keadilan Restoratif - Maknun, Luil; Widiyaswara, Riani (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
Abstract Benefits and restorative justice is a development of dispute resolution that can restore the rights of victims and the interests of the parties by providing justice. Settlement through penal mediation is the first step in an advocate's duties and is a form of providing legal assistance. The legal research used is normative juridical research. The activeness of advocates in implementing penal mediation can help achieve justice in resolving criminal cases. For this reason, socialization regarding restorative justice must be intensified in related institutions or agencies. In order to have a strong legal basis, it is necessary to create a special policy that regulates the concept of restorative justice in the criminal justice system in Indonesia. Keywords: Penal Mediation, Advocate, Restorative